Ethics : basic concepts and contemporary moral issues - Gualdo, Rosendo S. (Valenzuela City : Mega-Jesta Prints, Inc., 2000)
Ethics is a study for knowledge ; but more than that, it is a way of living. Moral educators impart the knowledge in the hope that they be translated into the daily living of the individual, the learner; to transform his life from unrighteousness to righteousness; to affirm and realize the ultimate meaning of his being.
Chapter I : Introduction -- Chapter II : Man and his existence -- Chapter III : Man and his ends -- Chapter IV : Human acts -- Chapter V : The Morality of human arts -- Chapter VI : Rights and duties -- Chapter VII : Marriage and sexuality -- Chapter VIII : The Human family -- Chapter IX : Human values -- Chapter X : Human work -- Chapter XI : Bioethical issues and their moral implications -- Chapter XII : Environmental ethics -- Chapter XIII : Death penalty : its moral implication.
Includes bibliographical references.
Keywords: ETHICS; ETHICS -- STUDY AND TEACHING -- PHILIPPINES